2007
DOI: 10.1037/0033-3204.44.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of the Multicultural Counseling Self-Efficacy Scale--Racial Diversity Form.

Abstract: The purpose of the study is to develop and validate the Multicultural Counseling Self-Efficacy Scale -Racial Diversity Form (MCSE-RD). Theoretical underpinnings of the study were derived from social cognitive theory and the literature of multicultural counseling. Specifically, the MCSE-RD is designed to assess the helping professional's perceived abilities in providing individual counseling to racially diverse clients. Data were collected from 181 graduate students in counselingrelated programs. Results of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 78 publications
(153 reference statements)
4
54
0
2
Order By: Relevance
“…Apart from Sheu and Lent's (2007) study, which found that trainees of color reported higher perceived multicultural counseling competence than White trainees when working with ethnically and racially diverse clients, little current research has focused on counselor multicultural CSE with respect to clients who represent a specific ethnicity or race. In particular, in this study, we empirically measured the multicultural CSE of counselors with respect to working with MEA clients.…”
Section: Trainee Race and Multicultural Competencementioning
confidence: 91%
See 2 more Smart Citations
“…Apart from Sheu and Lent's (2007) study, which found that trainees of color reported higher perceived multicultural counseling competence than White trainees when working with ethnically and racially diverse clients, little current research has focused on counselor multicultural CSE with respect to clients who represent a specific ethnicity or race. In particular, in this study, we empirically measured the multicultural CSE of counselors with respect to working with MEA clients.…”
Section: Trainee Race and Multicultural Competencementioning
confidence: 91%
“…Ladany et al (1997) found that trainees of color reported greater multicultural competence than White trainees when working with clients of color. Perhaps the greater multicultural competence of trainees of color is influenced by a greater sense of multicultural CSE in work with clients of color (Sheu & Lent, 2007). The CSE beliefs of counselors may drive them toward a specific area of expertise, client type, and/or clinical setting over time, which may allow them to focus on the clientele with whom they believe they do their best work.…”
Section: Trainee Race and Multicultural Competencementioning
confidence: 99%
See 1 more Smart Citation
“…This line of inquiry has produced a series of therapist self-efficacy scales such as the Addiction Counseling Self-Efficacy Scale (ACSES; Murdock, Wendler, & Nilsson, 2005), Multicultural Counseling Self-Efficacy Scale-Racial Diversity Form (MCSE-RD; Sheu & Lent, 2007), and the Lesbian, Gay, and Bisexual Affirmative Counseling Self-Efficacy Inventory (LGB-CSI; Dillon & Worthington, 2003). Moreover, several self-efficacy scales were utilized as outcome measures in training programs.…”
Section: Self-efficacy: Theory and Applicationmentioning
confidence: 99%
“…The two-week test-retest reliability correlations of the subscales ranged from .69 to .88 with the total score reliability correlation being .77 (Sheu & Lent, 2007).…”
Section: Participantsmentioning
confidence: 99%